2000
DOI: 10.1021/jo0008690
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling (MM2 and PM3) and Experimental (NMR and Thermal Analysis) Studies on the Inclusion Complex of Salbutamol and β-Cyclodextrin

Abstract: The inclusion complex of salbutamol and beta-cyclodextrin (beta-CD) is studied by computational (MM2 and PM3) and experimental techniques. Molecular modeling calculations predict two different orientations of salbutamol in the beta-CD cavity in vacuo and in aqueous solution. In vacuo calculations show that the introduction of the aromatic ring of salbutamol is preferred to the introduction of the tert-butyl group into the beta-CD cavity. However, in aqueous solution both computational methods predict the intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Similar ROESY cross peaks have been observed for the inclusion complexes formed between salbutamol and β-CD and for dexamethasone sodium phosphate and γ -CD. [31,32] The doxepin H-6, H-α, H-β, and H-γ resonances also have cross peaks only to the cyclodextrin H-3 proton that is located near the mouth of the cyclodextrin cavity. The cross peak between cyclodextrin H-3 and doxepin H-α is strongest of the nonaromatic protons followed by H-6, and then H-β, and H-γ .…”
Section: (A) For the B Ring H-b1 And H-b3 Resonancesmentioning
confidence: 99%
“…Similar ROESY cross peaks have been observed for the inclusion complexes formed between salbutamol and β-CD and for dexamethasone sodium phosphate and γ -CD. [31,32] The doxepin H-6, H-α, H-β, and H-γ resonances also have cross peaks only to the cyclodextrin H-3 proton that is located near the mouth of the cyclodextrin cavity. The cross peak between cyclodextrin H-3 and doxepin H-α is strongest of the nonaromatic protons followed by H-6, and then H-β, and H-γ .…”
Section: (A) For the B Ring H-b1 And H-b3 Resonancesmentioning
confidence: 99%
“…Similar ROESY cross peaks have been observed for inclusion complexes formed be tween doxepin and βCD, salbutamol and βCD, and between dexamethasone sodium phosphate and γCD. 22,28,29) Mean while, cross peaks between βCD and fumaric acid have not been observed. Therefore, it was suggested that fumaric acid was not included in the βCD cavity.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular modeling has become a useful technique for studying host–guest complexes, especially as a complement to structural studies on the orientation of the host in guest cavities 28–30. In this sense, we have carried out molecular mechanics calculations toward the determination of the geometrical conformation of DSP in the cavities of γ‐CyD and DIMEB.…”
Section: Resultsmentioning
confidence: 99%